Merokok Sebagai Faktor Risiko Terjadinya Solusio Plasenta - Sherly Melvinia Malia; Nurul Islamy; Ramadhan Triyandi (Medula, 2023)
Placental abruption is the separation of the placenta before the time of delivery arrives. Placental abruption is one of the causes of bleeding during labor. Placental abruption is rare in vaginal delivery. In 1.000 births as many as 228 thousand mothers die. Bleeding is the highest cause of maternal death with a proportion of 27%. The most common causes of antepartum bleeding include placenta previa, placental abruption, and other causes such as marginal sinus bleeding, cervicitis, vasa previa, infection, and genital trauma. Placental abruption occurs when the mother's blood vessels detach from the placenta, this causes bleeding between the lining of the uterus and the placenta. There are various risk factors that can cause placental abruption, namely age, parity, alcohol consumption, cocaine consumption, and smoking. it can cause decreased blood flow to the placenta. This occurs due to changes in vasoactive substances such as prostacyclin and nitric oxide, or also due to endothelial cell damage. Nicotine in cigarettes also has a vasoconstrictive effect that can occur in the uterine arteries and umbilical arteries and increases the concentration of hemoxihemoglobin which interferes with oxygenation. The ensuing hypoxia causes microinfarction of the clotting placenta which gives rise to necrotic foci These necrotic foci then develop and cause placental abruption.